DIALOGUE OF CIVILISATION: AN ISLAMIC PERSPECTIVE - Baharuddin, Azizan (Journal of Dharma, 2009)
To the 1.9 billion Muslims in the world today, the Quran and Hadiths are the most crucial sources of knowledge regarding their religion. In these sources, interfaith/cultural/civilisational dialogue is very much emphasized. It is perhaps unfortunate that despite the importance that Islam places on dialogue, many, beginning with Muslims themselves, do not know the body of teachings and literature concerning it. This subject is now growing very fast in its importance, especially after the unfortunate event of 9/11 as well as Samuel Huntington’s theory of ‘the clash of civilisations.’ As a response to these events, Muslims have initiated and participated in inter-civilisational dialogue at many different levels and in many different forms all over the world in the past 10 years.